Improving the Machining Process by Analysing the Relationship Between Cutting Force and Temperature in Drilling of Engineering Steels - Pavel Polák; Zuzana Poláková; Ján Žitňanský; Petr Dostál; Katarína Kollárová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
This paper describes the experiment of measuring the temperature and cutting force during the drilling of short holes without using cutting lubricants, at constant cutting speed, and at increasing shift. Measurement was performed on steel samples of grade 11 523. During drilling, temperature was monitored by a thermocouple, using the method of two foreign metals. Cutting force was measured by a strain-gauge sensor. The experiment provides a quick orientation in the given issue and points out to the optimisation of cutting conditions. Based on results, it can be stated that the range of temperatures and the size of cutting forces depends on technological conditions, cutting parameters, and mechanical and physical properties of tool and workpiece’s material.